Design and development of wide band dual-polarized magneto electric dipole antenna for mobile communications. Issue 2 (1st March 2019) - Pollayi, Lakshminarayana; Dasari, Rama Krishna; Pandharipande, Vijay M.
Abstract: A shorted magneto electric dipole with orthogonal dual polarization is designed for modern wireless communications. The proposed antenna is a wideband dual-polarized antenna consisting of magneto electric dipoles, which are fed by novel hook-shaped strip feeds. The antenna proposed in this paper is simulated using EM simulation software called high-frequency structure simulator. The simulated and measured results are presented. This antenna achieves 45.4% of impedance bandwidth of −10 dB RL for frequency range from 1.7 to 2.7 GHz. This frequency range covers the wireless communications applications like GSM 1800/1900, WCDMA, Bluetooth, Wi-Fi, etc.